Fluorescent and photoconductive nanoribbons as a dual-mode sensor for selective discrimination of alkyl amines versus aromatic amines. Issue 81 (27th August 2015) - Zhang, Yibin; Peng, Cheng; Ma, Xiaojie; Che, Yanke; Zhao, Jincai
Abstract : Nanoribbons were used as a dual-mode sensor, which exhibited orthogonal responses when exposed to alkyl amines versus aromatic amines. Abstract : Highly fluorescent and photoconductive nanoribbons assembled from an asymmetric perylene diimide (PDI) were used as a dual-mode sensor for sensitive and selective discrimination of two classes of organic amines in the vapor phase, i.e., alkyl amines and aromatic amines.